Domestic low-foam easy-bleaching laundry gel bead and preparation method thereof

By using a ternary compound surfactant system and nano-silica modified PVA membrane material, the problems of detergency and low-temperature dissolution of low-foam laundry pods have been solved, achieving a high-efficiency washing effect that is low-foaming, easy to rinse, water-saving, and energy-saving.

CN120843202APending Publication Date: 2025-10-28GUANGZHOU DABAI BIOLOGICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510966342.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-14
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing low-foam laundry detergent pods have the problem that the low-foam surfactant system cannot achieve both detergency and the film material does not dissolve completely in low-temperature environments.

Method used

A ternary compound surfactant system consisting of ethoxylated fatty alcohol sulfate, alkyl glycoside, and cocamidopropyl betaine was adopted. Combined with gradient emulsification-ultrasonic dispersion process and nano-silica modified PVA membrane material, the micelle structure was optimized and the nano-sized particle size was controlled. The modified membrane material reduced crystallinity through interfacial coupling to improve hydrophilicity and dissolution rate.

Benefits of technology

It significantly improves cleaning power while reducing foam generation, ensuring that the detergent ingredients dissolve quickly in cold water, reducing the number of rinses and chemical residues, achieving high-efficiency washing at low temperatures and reducing chemical residues on clothes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120843202A_ABST
    Figure CN120843202A_ABST
Patent Text Reader

Abstract

The invention discloses a household low-foam easy-to-bleach laundry condensate bead and a preparation method thereof, and relates to the technical field of daily chemical product manufacturing, and the preparation method comprises the following steps: adding alkyl glycoside in three times, simultaneously starting an ultrasonic generation device, forming a nano-scale dispersion system, cooling and increasing the stirring speed, and forming a microemulsion. The invention has the following advantages: by adopting a ternary compound surfactant system of ethoxylated fatty alcohol sulfate, alkyl glycoside and cocamidopropyl betaine, and matching with a gradient emulsification-ultrasonic dispersion process and the nano-silica modified PVA membrane material, the defect that low-foam performance and detergency are difficult to cooperate in the prior art is overcome; the ternary compound system optimizes the micelle structure through the synergistic effect of the surfactants, and the ultrasonic dispersion process realizes nanoscale particle size control so as to enhance the decontamination activity, so that the generation of foam is reduced, the decontamination capability is remarkably improved, the rinsing frequency and chemical residues are reduced, and the effects of saving water and energy and cleaning and protecting clothes are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of daily chemical product manufacturing technology, specifically to a low-foaming, easy-to-rinse laundry detergent pod for household use and its preparation method. Background Technology

[0002] With the upgrading and iteration of household laundry products, laundry pods, as a new type of laundry product that integrates high efficiency, convenience and precise measurement, have gradually become the mainstream in the market. Traditional laundry powder and liquid laundry detergent have problems such as inconvenient dosage control, high residue rate of washing ingredients and environmental pollution. Laundry pods, on the other hand, encapsulate concentrated washing liquid with water-soluble film material, realizing the precise use mode of "one pod for one wash", effectively solving the pain points of traditional products.

[0003] Existing low-foam laundry pods have a double defect:

[0004] ① Low-foaming surfactant systems are difficult to balance detergency;

[0005] ② The membrane material does not dissolve completely in a low-temperature environment, resulting in insufficient release of effective ingredients;

[0006] Therefore, we propose a low-foaming, easy-to-rinse laundry detergent pod for household use and its preparation method. Summary of the Invention

[0007] The purpose of this invention is to provide a low-foaming, easy-to-rinse laundry detergent pod for household use and its preparation method.

[0008] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing low-foaming, easy-to-rinse laundry detergent pods for household use, comprising a preparation method, wherein the preparation method includes:

[0009] Step 1: Weigh out ethoxylated fatty alcohol sulfate, alkyl glycoside, cocamidopropyl betaine and deionized water. Mix the ethoxylated fatty alcohol sulfate and cocamidopropyl betaine in advance and filter.

[0010] Step 2: Add the filtered mixture to the jacketed reactor, dissolve it in deionized water, and adjust the pH of the system.

[0011] Step 3: Add alkyl glycosides in three batches while simultaneously activating the ultrasonic generator to form a nanoscale dispersion system. Cool down and increase the stirring rate to form a microemulsion.

[0012] Step 4: Add polycarboxylate detergent, sodium citrate and disodium EDTA to the microemulsion, stir, and control the viscosity of the detergent solution;

[0013] Step 5: Add polyvinyl alcohol and nano silica modifier to deionized water to prepare modified PVA film solution. Take a portion of the solution and coat it onto PET release film. Dry and cure the film, and then test its performance. Store the remaining solution.

[0014] Step 6: Inject the washing solution into the modified PVA membrane solution to form spherical droplets. After drying and solidification, the droplets are placed into a vacuum forming mold for shaping, and the amount of washing solution filled into each droplet is controlled.

[0015] Step 7: Conduct a full range of tests on the formed beads, and package and store them after passing the tests.

[0016] As a further aspect of the present invention: In step one, 15%-20% ethoxylated fatty alcohol sulfate (AES), 8%-12% alkyl glycoside (APG), and 5%-8% cocamidopropyl betaine (CAPB) are weighed according to mass percentage, and 45%-55% deionized water is used as the base solvent. The ethoxylated fatty alcohol sulfate and cocamidopropyl betaine are premixed at 60℃-65℃, and microfiltration is performed using a polytetrafluoroethylene membrane with a pore size of 0.22μm-0.25μm at a temperature above 50℃ to remove particulate matter and ensure the homogeneity of the subsequent dissolution process.

[0017] As a further aspect of the present invention: In step two, the filtered mixture of ethoxylated fatty alcohol sulfate and cocamidopropyl betaine is added to a jacketed reactor and dissolved in deionized water at a stirring rate of 80 rpm to 100 rpm under constant temperature conditions of 50℃-60℃. The mixture is stirred continuously for 10 min to 15 min until a transparent homogeneous solution is formed. The pH of the solution is monitored in real time by an online pH sensor, and a sodium hydroxide solution with a mass concentration of 5% to 6% is added dropwise to adjust the pH of the system to a weakly alkaline range of 7.5-8.5, creating a suitable environment for the subsequent compounding reaction.

[0018] As a further aspect of the present invention: In step three, alkyl glycosides are added in equal amounts three times at 5-6 minute intervals. After each addition, stirring is maintained for 2-5 minutes to allow the materials to be initially mixed. Simultaneously, the ultrasonic generator is activated, and the ultrasonic frequency is controlled at 20kHz-40kHz with a power density of 0.5W / cm³. 2 -1.0W / cm 2 The surfactant molecules are dispersed in a nanoscale system under the cavitation effect. The dynamic light scattering particle size analyzer is used to monitor the particle size in real time. When the surfactant particle size is stable at 100nm-200nm, the ultrasonic treatment is stopped. Then the reaction temperature is reduced to 30℃-40℃, and the stirring rate is increased to 200rpm-300rpm and maintained for 30min-35min to form a thermodynamically stable microemulsion.

[0019] As a further aspect of the present invention: In step four, 4%-6% of polycarboxylate detergent (such as sodium polyacrylate with a weight average molecular weight of 8000-12000), 2%-3% sodium citrate, and 0.5-1% disodium ethylenediaminetetraacetate (EDTA-2Na) are added sequentially to the microemulsion. The mixture is stirred for 45-55 minutes at 25℃-30℃ and 150rpm-200rpm to remove residual calcium and magnesium ions in the system through a chelation reaction (chelation value ≥300mgCaCO3 / g). At the same time, the buffering effect of sodium citrate is used to maintain the pH value stability. Finally, the viscosity of the washing liquid is controlled to be 300mPa·s-500mPa·s at 25℃-28℃ by rotational viscometer detection.

[0020] As a further aspect of the present invention: In step five, 90%-95% polyvinyl alcohol (PVA, degree of polymerization 1750±50) and 5%-10% nano-silica modifier with a particle size of 20nm-50nm are added to deionized water at a solid-liquid mass ratio of 1:4-5. The mixture is dispersed under high-speed shear at 80℃-90℃ and 4000rpm-4500rpm for 30min-35min, and then stirred and dissolved for 2h-2.5h at 300rpm-400rpm to form a transparent and viscous modified PVA film solution. A portion of this solution is then taken. The solution is uniformly coated onto the PET release film using a casting machine. The film thickness is controlled to be 20μm-30μm by adjusting the gap of the casting machine blades. The coated film is then sent into a hot air circulating drying oven and cured at 50℃-60℃ for 12h-15h. Performance testing is then performed, requiring an elongation at break ≥200% and a critical water solubility temperature ≤15℃. If the requirements are not met, the ratio of polyvinyl alcohol to nano silica is adjusted and the film is prepared again. Once the requirements are met, it is used as a solid film material. The remaining solution is stored in a sealed container under nitrogen protection at a temperature of 20-25℃.

[0021] As a further aspect of the present invention: In step six, a dual-chamber diaphragm pump is used to inject the inner phase washing liquid into the outer phase modified PVA membrane material solution at a flow rate of 0.8 mL / s-1.2 mL / s. The solution is then formed into spherical droplets with a diameter of 18 mm-22 mm by a coaxial spray device. The droplets are then surface-cured for 10-15 seconds in a drying channel with a temperature of 25℃-35℃ and a humidity of 55%-65%. Subsequently, the droplets are shaped by a vacuum forming mold (pressure 50-80 kPa) to form a uniform coating layer at the membrane material interface. The amount of washing liquid filling per droplet is controlled to be 8 g-10 g.

[0022] As a further aspect of the present invention: In step seven, the formed beads undergo comprehensive testing: ① The ion concentration of the rinsing solution is measured using a conductivity meter and converted to residual amount using a standard curve. The residual ion concentration on the fabric surface after washing is required to be ≤0.3mg / cm³. 2② The foam height was detected using a Ross-Myers foam meter, and the initial foam height was controlled to be ≤15mm. The foam decay rate was ≥60% in 5min-6min. ③ The critical micelle concentration was determined by UV-Vis spectrophotometer using the Rhodamine B solubilization method, and the control value was 0.08mmol / L-0.12mmol / L.

[0023] The tested and qualified beads are individually packaged with aluminum-plastic composite film, and the final product is stored in an environment with a temperature of ≤25℃ and a humidity of ≤60%.

[0024] In addition, this application also provides a household low-foaming and easy-to-rinse laundry detergent pod, which is prepared by a method for preparing household low-foaming and easy-to-rinse laundry detergent pods.

[0025] Compared with the prior art, the beneficial effects of the present invention by adopting the above technical solution are as follows:

[0026] 1. This invention utilizes a ternary compound surfactant system of ethoxylated fatty alcohol sulfate, alkyl glycoside, and cocamidopropyl betaine, combined with a gradient emulsification-ultrasonic dispersion process and nano-silica modified PVA membrane material. This solves the problem of difficulty in synergistically achieving low foaming performance and detergency in existing technologies. The ternary compound system optimizes the micelle structure through the synergistic effect between surfactants, the ultrasonic dispersion process achieves nanoscale particle size control to enhance detergency, and the modified membrane material precisely controls the dissolution rate to ensure efficient release of components. Thus, while reducing foam generation, it significantly improves detergency, reduces the number of rinsing cycles and chemical residues, and achieves water-saving, energy-saving, and clean garment protection effects.

[0027] 2. This invention solves the defect of incomplete dissolution of the film material in low-temperature environments in the prior art by using a PVA film material modified with nano-silica and a matching casting and curing process. The modified film material reduces the crystallinity of the film material and improves its hydrophilicity through the interfacial coupling effect between nano-silica and PVA molecules. Combined with the temperature gradient curing process to optimize the molecular chain arrangement, the critical temperature for water solubility of the film material is lowered. This enables the laundry pods to dissolve quickly in cold water, ensuring the full release of washing ingredients and avoiding the problem of incomplete washing caused by film material residue. At the same time, it improves the applicability of the quick wash mode, achieving the effect of low-temperature and efficient washing and reducing chemical residues on clothes. Attached Figure Description

[0028] Figure 1 This is a schematic diagram of the ultrasonic dispersion-nanofilm synergistic process in an embodiment of the present invention;

[0029] Figure 2 This is a schematic diagram of the method steps in an embodiment of the present invention. Detailed Implementation

[0030] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings. It should be noted that the description of these embodiments is for the purpose of helping to understand the present invention, but does not constitute a limitation of the present invention.

[0031] Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0032] Please see the appendix Figure 1 -Appendix Figure 2 This invention discloses a method for preparing low-foaming, easy-to-rinse laundry detergent pods for household use, comprising the following preparation method:

[0033] Step 1: Weigh out ethoxylated fatty alcohol sulfate, alkyl glycoside, cocamidopropyl betaine and deionized water. Mix the ethoxylated fatty alcohol sulfate and cocamidopropyl betaine in advance and filter.

[0034] Step 2: Add the filtered mixture to the jacketed reactor, dissolve it in deionized water, and adjust the pH of the system.

[0035] Step 3: Add alkyl glycosides in three batches while simultaneously activating the ultrasonic generator to form a nanoscale dispersion system. Cool down and increase the stirring rate to form a microemulsion.

[0036] Step 4: Add polycarboxylate detergent, sodium citrate and disodium EDTA to the microemulsion, stir, and control the viscosity of the detergent solution;

[0037] Step 5: Add polyvinyl alcohol and nano silica modifier to deionized water to prepare modified PVA film solution. Take a portion of the solution and coat it onto PET release film. Dry and cure the film, and then test its performance. Store the remaining solution.

[0038] Step 6: Inject the washing solution into the modified PVA membrane solution to form spherical droplets. After drying and solidification, the droplets are placed into a vacuum forming mold for shaping, and the amount of washing solution filled into each droplet is controlled.

[0039] Step 7: Conduct a full range of tests on the formed beads, and package and store them after passing the tests.

[0040] In one embodiment of the present invention: In step one, 15%-20% ethoxylated fatty alcohol sulfate (AES), 8%-12% alkyl glycoside (APG) and 5%-8% cocamidopropyl betaine (CAPB) are weighed according to mass percentage, and 45%-55% deionized water is used as the base solvent. The ethoxylated fatty alcohol sulfate and cocamidopropyl betaine are premixed at 60°C-65°C, and microfiltration is performed using a polytetrafluoroethylene membrane with a pore size of 0.22μm-0.25μm at a temperature above 50°C to remove particulate matter and ensure the homogeneity of the subsequent dissolution process.

[0041] In one embodiment of the present invention: In step two, the filtered mixture of ethoxylated fatty alcohol sulfate and cocamidopropyl betaine is added to a jacketed reactor and dissolved in deionized water at a stirring rate of 80 rpm to 100 rpm under constant temperature conditions of 50℃-60℃. The mixture is stirred for 10 min to 15 min until a transparent homogeneous solution is formed. The pH of the solution is monitored in real time by an online pH sensor. A sodium hydroxide solution with a mass concentration of 5% to 6% is added dropwise to adjust the pH of the system to a weakly alkaline range of 7.5 to 8.5, creating a suitable environment for the subsequent compounding reaction.

[0042] In one embodiment of the present invention: In step three, alkyl glycosides are added in equal amounts three times at 5-6 minute intervals. After each addition, stirring is maintained for 2-5 minutes to allow the materials to be initially mixed. At the same time, the ultrasonic generator is started, and the ultrasonic frequency is controlled at 20kHz-40kHz and the power density at 0.5W / cm³. 2 -1.0W / cm 2 The surfactant molecules are dispersed in a nanoscale system under the cavitation effect. The dynamic light scattering particle size analyzer is used to monitor the particle size in real time. When the surfactant particle size is stable at 100nm-200nm, the ultrasonic treatment is stopped. Then the reaction temperature is reduced to 30℃-40℃, and the stirring rate is increased to 200rpm-300rpm and maintained for 30min-35min to form a thermodynamically stable microemulsion.

[0043] In one embodiment of the present invention: In step four, 4%-6% of polycarboxylate detergent (such as sodium polyacrylate with a weight average molecular weight of 8000-12000), 2%-3% sodium citrate, and 0.5-1% disodium ethylenediaminetetraacetate (EDTA-2Na) are added sequentially to the microemulsion. The mixture is stirred for 45-55 minutes at 25℃-30℃ and 150rpm-200rpm to remove residual calcium and magnesium ions in the system through a chelation reaction (chelation value ≥300mgCaCO3 / g). At the same time, the pH value is maintained by utilizing the buffering effect of sodium citrate. Finally, the viscosity of the washing liquid is controlled to be 300mPa·s-500mPa·s at 25℃-28℃ by rotational viscometer detection.

[0044] In one embodiment of the present invention: In step five, 90%-95% polyvinyl alcohol (PVA, degree of polymerization 1750±50) and 5%-10% nano-silica modifier with a particle size of 20nm-50nm are added to deionized water, with a solid-liquid mass ratio of 1:4-5. The mixture is then dispersed at 80℃-90℃ and 4000rpm-4500rpm for 30-35 minutes under high-speed shear dispersion (the nano-silica disrupts the regular arrangement of PVA molecular chains through interfacial coupling, reducing the crystallinity to ≤25% (XRD determination), and exposing hydrophilic groups lowers the critical dissolution temperature), and stirred at 300rpm-400rpm. Stir and dissolve for 2-2.5 hours to form a transparent and viscous modified PVA film solution. Take a portion of the solution and evenly coat it onto a PET release film using a casting machine. Control the film thickness to 20μm-30μm by adjusting the gap of the casting machine blades. Send the coated film into a hot air circulating drying oven and cure it at 50℃-60℃ for 12-15 hours. Then, conduct performance testing, requiring an elongation at break ≥200% and a critical water solubility temperature ≤15℃. If the requirements are not met, adjust the ratio of polyvinyl alcohol to nano silica and re-prepare. Once the requirements are met, use it as a solid film material. Store the remaining solution in a sealed container under nitrogen protection at 20-25℃.

[0045] In one embodiment of the present invention: In step six, the inner phase washing liquid is injected into the outer phase modified PVA membrane material solution at a flow rate of 0.8 mL / s-1.2 mL / s using a dual-chamber diaphragm pump. Spherical droplets with a diameter of 18 mm-22 mm are formed by a coaxial spray device. The droplets are then surface-cured for 10-15 seconds in a drying channel with a temperature of 25℃-35℃ and a humidity of 55%-65%. Subsequently, they are shaped by a vacuum forming mold (pressure 50-80 kPa) to form a uniform coating layer at the membrane material interface. The amount of washing liquid filling per droplet is controlled to be 8 g-10 g.

[0046] In one embodiment of the present invention: In step seven, the formed beads undergo comprehensive testing: ① The ion concentration of the rinsing solution is measured using a conductivity meter and converted to residual amount using a standard curve. The residual ion concentration on the fabric surface after washing is required to be ≤0.3mg / cm³. 2 ② The foam height was detected using a Ross-Myers foam meter, and the initial foam height was controlled to be ≤15mm. The foam decay rate was ≥60% in 5min-6min. ③ The critical micelle concentration was determined by UV-Vis spectrophotometer using the Rhodamine B solubilization method, and the control value was 0.08mmol / L-0.12mmol / L.

[0047] The tested and qualified beads are individually packaged with aluminum-plastic composite film, and the final product is stored in an environment with a temperature of ≤25℃ and a humidity of ≤60%.

[0048] Example 1, please refer to the appendix. Figure 1-Appendix Figure 2 Preparation and performance testing of low-foaming, easy-rinse laundry detergent pods for household use:

[0049] I. Preparation Steps

[0050] Raw material pretreatment:

[0051] Weigh out 17.5% ethoxylated fatty alcohol sulfate (AES), 10% alkyl glycoside (APG), and 6.5% cocamidopropyl betaine (CAPB) by mass percentage, add 66% deionized water (total mass 1000g), mix AES and CAPB at 62℃, and filter using a 0.22μm polytetrafluoroethylene membrane at 55℃ to remove impurity particles.

[0052] Pre-dissolution and pH adjustment:

[0053] Add the filtered mixture to a 5L jacketed reactor and dissolve it in deionized water at 55℃ with a stirring rate of 90 rpm. Stir for 12 minutes until a clear solution is obtained, then add 5.5% sodium hydroxide solution dropwise to adjust the pH to 8.0.

[0054] Gradient emulsification-ultrasonic dispersion:

[0055] APG was added in three batches (5 minutes apart), with stirring for 3 minutes after each addition. The ultrasonic device was then activated (frequency 30 kHz, power density 0.75 W / cm³). 2 When the particle size detected by dynamic light scattering stabilizes at 150 nm, stop the sonication, cool down to 35 °C, and stir at 250 rpm for 32 min to form a microemulsion.

[0056] Builder formulation:

[0057] Add 5% sodium polyacrylate with a weight average molecular weight of 10,000, 2.5% sodium citrate, and 0.75% EDTA-2Na, and stir at 180 rpm for 50 min at 28℃, controlling the viscosity at 25℃ to 400 mPa·s.

[0058] Preparation of modified membrane materials:

[0059] 92.5% PVA (degree of polymerization 1750) and 7.5% nano-silica (particle size 30nm) were added to deionized water at a solid-liquid ratio of 1:4.5. The mixture was sheared at 4200rpm for 32min at 85℃ and then stirred at 350rpm for 2.2h to obtain a film solution. A portion of the solution was cast and coated onto a PET film (film thickness 25μm) and dried at 55℃ for 13h. The elongation at break was 220% and the critical temperature for water solubility was 12℃.

[0060] Bead formation:

[0061] The washing solution was injected into the membrane solution at a flow rate of 1.0 mL / s using a dual-chamber diaphragm pump. The solution was coaxially sprayed to form 20 mm spherical droplets. After drying at 30°C and 60% humidity for 12 s, the solution was shaped using a vacuum forming mold (65 kPa) with a single filler weight of 9 g.

[0062] Testing and Packaging:

[0063] The detected residual ion concentration was 0.2 mg / cm³. 2 The initial foam height is 12mm (65% decay rate in 5 minutes), the CMC is 0.10mmol / L, and it is stored in an environment of 20℃ and 50% humidity after being packaged in aluminum-plastic packaging.

[0064] II. Performance Test Results

[0065] Cleaning power: 92% stain removal rate for smeared cloths with sebum (GB / T13174 standard), which is 24% higher than commercially available low-foaming gel beads;

[0066] Foam control: The foam height is always ≤15mm during the standard washing cycle of the washing machine, and the number of rinses is reduced by 1.

[0067] Low-temperature solubility: Completely dissolves in 10℃ water in 3 minutes; 90% of the ingredients are released in the quick wash mode (15 minutes).

[0068] Example 2, please refer to the appendix. Figure 1 -Appendix Figure 2 Preparation of low-foaming, easy-rinse laundry detergent pods specifically for hard water environments:

[0069] I. Preparation Steps

[0070] Raw material pretreatment:

[0071] Weigh 20% AES, 8% APG, 5% CAPB, and 67% deionized water (total mass 1000g). Mix AES and CAPB at 65℃ and filter with a 0.25μm polytetrafluoroethylene membrane at 50℃.

[0072] Pre-dissolution and pH adjustment:

[0073] Stir at 80 rpm for 15 min at 50°C in a jacketed reactor, and adjust the pH to 7.5 (5% sodium hydroxide solution).

[0074] Gradient emulsification-ultrasonic dispersion:

[0075] APG was added in three batches (6 minutes apart), with stirring for 5 minutes each time. Ultrasonic conditions: frequency 20 kHz, power density 1.0 W / cm³. 2 When the particle size stabilizes at 200 nm, the temperature is lowered to 30 °C and stirred at 300 rpm for 35 min.

[0076] Builder formulation:

[0077] Add 6% sodium polyacrylate (weight average molecular weight 8000), 3% sodium citrate, and 1% EDTA-2Na. Stir at 150 rpm for 55 min at 25°C. The viscosity is 300 mPa·s at 28°C.

[0078] Preparation of modified membrane materials:

[0079] 90% PVA and 10% nano-silica (particle size 50nm) were mixed at a solid-liquid ratio of 1:5, sheared at 4500rpm for 35min at 80℃, stirred at 300rpm for 2.5h, and cast into a film with a thickness of 30μm. The film was dried at 60℃ for 12h, with an elongation at break of 200% and a critical temperature for water solubility of 15℃.

[0080] Bead formation:

[0081] The washing liquid flow rate is 0.8 mL / s, forming 18 mm droplets. It is dried at 25°C and 55% humidity for 15 seconds, and then shaped in a vacuum mold (50 kPa). The single-particle filling amount is 8 g.

[0082] Testing and Packaging:

[0083] Residual ion concentration: 0.25 mg / cm³ 2 Initial foam height 15mm (60% decay rate in 5min), CMC 0.08mmol / L, stored in aluminum-plastic packaging.

[0084] II. Performance Test Results

[0085] Hard water adaptability: 88% cleaning efficiency in 300ppm hard water, 38% better than commercially available products;

[0086] Foam control: The foam height increases by only 2mm when washing with hard water compared to soft water;

[0087] Rinsing ease: Residual amount ≤0.3mg / cm³ after rinsing twice. 2 It meets the washing standards for infant and toddler clothing.

[0088] Based on the above embodiments, it can be concluded that by employing a ternary compound surfactant system, a gradient emulsification-ultrasonic dispersion process, and nano-silica modified PVA membrane material, the shortcomings of existing technologies, such as the difficulty in synergistic effects between low-foaming performance and detergency, and the incomplete dissolution of membrane materials at low temperatures, are effectively solved. The ternary compound system optimizes the micelle structure through the synergistic effect of surfactants, the ultrasonic process achieves nanoscale particle size control to enhance detergency, and the modified membrane material reduces crystallinity and increases hydrophilicity through interfacial coupling, precisely controlling the dissolution rate. Thus, while reducing foam generation, the detergency is significantly improved, achieving complete dissolution in 3 minutes in a 10℃ cold water environment, a hard water detergency rate of 88%, and reducing the number of rinsing cycles by one, with a residual ion concentration ≤0.3mg / cm³. 2By leveraging the synergistic effects of various processes and technologies, it can achieve a high-efficiency washing effect that is low-foaming, easy to rinse, water-saving, energy-saving, and adaptable to multiple scenarios.

[0089] While the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the invention. Any variations and modifications can be made by those skilled in the art without departing from the spirit and scope of the invention. Therefore, any modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the technical solution of the present invention are not permitted.

[0090] All of these fall within the protection scope defined by the claims of this invention.

Claims

1. A method for preparing low-foaming, easy-to-rinse laundry detergent pods for household use, comprising a preparation method, characterized in that, The preparation method includes: Step 1: Weigh out ethoxylated fatty alcohol sulfate, alkyl glycoside, cocamidopropyl betaine and deionized water. Mix the ethoxylated fatty alcohol sulfate and cocamidopropyl betaine in advance and filter. Step 2: Add the filtered mixture to the jacketed reactor, dissolve it in deionized water, and adjust the pH of the system. Step 3: Add alkyl glycosides in three batches while simultaneously activating the ultrasonic generator to form a nanoscale dispersion system. Cool down and increase the stirring rate to form a microemulsion. Step 4: Add polycarboxylate detergent, sodium citrate and disodium EDTA to the microemulsion, stir, and control the viscosity of the detergent solution; Step 5: Add polyvinyl alcohol and nano silica modifier to deionized water to prepare modified PVA film solution. Take a portion of the solution and coat it onto PET release film. Dry and cure the film, and then test its performance. Store the remaining solution. Step 6: Inject the washing liquid into the modified PVA membrane solution to form spherical droplets. After drying and solidification, the droplets are placed into a vacuum forming mold for shaping, and the amount of washing liquid filling in each droplet is controlled. Step 7: Conduct a full range of tests on the formed beads, and package and store them after passing the tests.

2. The method for preparing a low-foaming, easy-to-rinse laundry detergent pod for household use according to claim 1, characterized in that: In step one, 15%-20% ethoxylated fatty alcohol sulfate, 8%-12% alkyl glycoside, and 5%-8% cocamidopropyl betaine are weighed according to mass percentage, and 45%-55% deionized water is used as the base solvent. The ethoxylated fatty alcohol sulfate and cocamidopropyl betaine are premixed at 60℃-65℃, and microfiltration is performed using a polytetrafluoroethylene membrane with a pore size of 0.22μm-0.25μm at a temperature above 50℃ to remove particulate matter.

3. The method for preparing a low-foaming, easy-to-rinse laundry detergent pod for household use according to claim 2, characterized in that: In step two, the filtered mixture of ethoxylated fatty alcohol sulfate and cocamidopropyl betaine is added to a jacketed reactor and dissolved in deionized water at a stirring rate of 80 rpm to 100 rpm under a constant temperature of 50℃-60℃. The mixture is stirred for 10 min to 15 min until a transparent homogeneous solution is formed. The pH of the solution is monitored in real time by an online pH sensor, and a 5%-6% sodium hydroxide solution is added dropwise to adjust the pH of the system to a weakly alkaline range of 7.5-8.

5.

4. The method for preparing a low-foaming, easy-to-rinse laundry detergent pod for household use according to claim 1, characterized in that: In step three, the alkyl glycoside is added in three equal portions at 5-6 minute intervals. After each addition, stirring is maintained for 2-5 minutes to allow the material to be initially mixed. Simultaneously, the ultrasonic generator is activated, with the ultrasonic frequency controlled at 20kHz-40kHz and the power density at 0.5W / cm³. 2 -1.0W / cm 2 The surfactant molecules are dispersed in a nanoscale system under the cavitation effect. The dynamic light scattering particle size analyzer is used to monitor the particle size in real time. When the surfactant particle size is stable at 100nm-200nm, the ultrasonic treatment is stopped. Then the reaction temperature is reduced to 30℃-40℃, and the stirring rate is increased to 200rpm-300rpm and maintained for 30min-35min to form a thermodynamically stable microemulsion.

5. The method for preparing a low-foaming, easy-to-rinse laundry detergent pod for household use according to claim 1, characterized in that: In step four, 4%-6% polycarboxylate detergent builder, 2%-3% sodium citrate, and 0.5-1% disodium ethylenediaminetetraacetate are added sequentially to the microemulsion. The mixture is stirred for 45-55 minutes at 25℃-30℃ and 150-200 rpm to remove residual calcium and magnesium ions from the system through a chelation reaction. At the same time, the buffering effect of sodium citrate is used to maintain pH stability. Finally, the viscosity of the washing liquid is controlled to be 300 mPa·s-500 mPa·s at 25℃-28℃ by rotational viscometer measurement.

6. The method for preparing a low-foaming, easy-to-rinse laundry detergent pod for household use according to claim 1, characterized in that: In step five, 90%-95% polyvinyl alcohol and 5%-10% nano-silica modifier with a particle size of 20nm-50nm are added to deionized water at a solid-liquid mass ratio of 1:4-5. The mixture is dispersed under high-speed shear at 80℃-90℃ and 4000rpm-4500rpm for 30-35 minutes, and then stirred and dissolved for 2-2.5 hours at 300rpm-400rpm to form a transparent, viscous modified PVA film solution. A portion of the solution is then uniformly coated using a casting machine. On PET release film, the film thickness is controlled to be 20μm-30μm by adjusting the gap of the casting machine blade. The coated film is then sent into a hot air circulating drying oven and cured at 50℃-60℃ for 12h-15h. Performance testing is then carried out, requiring an elongation at break of ≥200% and a critical water solubility temperature of ≤15℃. If the standards are not met, the ratio of polyvinyl alcohol to nano silica is adjusted and the film is prepared again. Once the standards are met, it is used as a solid film material. The remaining solution is stored in a sealed container under nitrogen protection at a temperature of 20-25℃.

7. The method for preparing a low-foaming, easy-to-rinse laundry detergent pod for household use according to claim 1, characterized in that: In step six, a dual-chamber diaphragm pump is used to inject the inner phase washing solution into the outer phase modified PVA membrane solution at a flow rate of 0.8 mL / s-1.2 mL / s. The solution is then sprayed through a coaxial spray device to form spherical droplets with a diameter of 18 mm-22 mm. The droplets are then surface-cured for 10-15 seconds in a drying channel with a temperature of 25℃-35℃ and a humidity of 55%-65%. Subsequently, the droplets are shaped in a vacuum forming mold to form a uniform coating layer at the membrane interface. The amount of washing solution filling per droplet is controlled to be 8 g-10 g.

8. The method for preparing a low-foaming, easy-to-rinse laundry detergent pod for household use according to claim 1, characterized in that: In step seven, a full range of tests are performed on the formed beads: ① The ion concentration of the rinsing solution is measured using a conductivity meter and converted to residual amount using a standard curve. The requirement is that the residual ion concentration on the fabric surface after washing is ≤0.3mg / cm³. 2 ② The foam height was detected using a Ross-Myers foam meter, and the initial foam height was controlled to be ≤15mm. The foam decay rate was ≥60% in 5min-6min. ③ The critical micelle concentration was determined by UV-Vis spectrophotometer using the Rhodamine B solubilization method, and the control value was 0.08 mmol / L-0.12 mmol / L. The tested and qualified beads are individually packaged with aluminum-plastic composite film, and the final product is stored in an environment with a temperature of ≤25℃ and a humidity of ≤60%.

9. A laundry pod suitable for the preparation method of the household low-foaming, easy-rinse laundry pod according to any one of claims 1-8, characterized in that, The laundry detergent pods are prepared using a method for preparing low-foaming, easy-to-rinse laundry detergent pods for household use.